Percutaneous Transpedicular Intravertebral Cage Augmentation with Short-Segment Fixation Using Specially Designed Cannulated Cage Trials for Advanced Kümmell Disease: A Preliminary Study Comparing with Vertebroplasty with Short-Segment Fixation - Park, Sung Cheol; Cheh, Gene; Kim, Yongjung; Chung, Hoon-Jae; Kang, Min-Seok; Choi, Ji-Hye (Clinics in orthopedic surgery, 2025)
The treatment of Kümmell disease (KD) is controversial. Corpectomy and reconstruction or osteotomy with long-level fusion was traditionally performed for the advanced KD. However, these procedures can be disadvantageous for elderly patients. Several alternative surgical procedures including transpedicular intravertebral cage augmentation (TPICA) or vertebroplasty (VP) combined with short-segment fixation (SSF) have been suggested to minimize the surgical burden. This study aimed to compare the outcomes of percutaneous TPICA plus SSF with VP plus SSF for advanced thoracolumbar (T11-L2) KD and to introduce our novel percutaneous TPICA technique using specially designed cannulated cage trials. We devised specially designed cannulated cage trials to make the TPICA procedure safer and more reproducible, minimizing the risk of the pedicle medial wall violation. All consecutive patients who underwent percutaneous TPICA or VP combined with SSF for advanced thoracolumbar KD, from January 2021 to June 2022, with ≥ 1-year follow-up at a single institution, were included. Perioperative details, clinical outcomes (visual analog scale and Oswestry Disability Index), and radiological outcomes (anterior vertebral body compression percentage and vertebral kyphotic angle [VKA] of the fractured vertebra, and local Cobb angle [LCA]) were collected and compared between the groups. A total of 42 patients were enrolled, with 21 patients in each group. There were no patients with pedicle medial wall fracture in the TPICA group. Both procedures provided significantly favorable radiological outcomes compared to those preoperatively. No significant differences were observed in the changes over time in all radiological parameters between the groups. Loss of correction during the follow-up period was significantly smaller in patients with TPICA than in those with VP in VKA (median [interquartile range], 2.15 [0.30-2.80] vs. 2.90 [0.90-6.53]; = 0.030) and LCA (2.70 ± 2.90 vs. 5.17 ± 4.40, = 0.037). Both procedures are minimally invasive and useful options for advanced KD, especially for elderly patients with high comorbidity. Our novel percutaneous TPICA technique using cannulated cage trials, being safer and more reproducible, may allow spine surgeons to easily perform TPICA.